P100 wave latency in anisometropic and esotropic amblyopia versus normal eyes - Saeedeh Hosseinmenni; Mohamad Reza Talebnejad; Ebrahim Jafarzadehpur; Ali Mirzajani; Enayatollah Osroosh (Journal of Ophthalmic & Vision Research, 2015)
Purpose: To evaluate cortical activity using pattern visual evoked potentials (PVEPs) in patients with mild and moderate amblyopia (esotropic and anisometropic). Methods: PVEP was recorded in 43 unilateral amblyopic patients, including 15 esotropic (ET) and 28 anisometropic (AM) patients, selected from three different medical centers in the city of Shiraz, Iran and compared to that obtained from 15 age and sex matched normal subjects who served as controls. Visual acuity (VA) in amblyopic eyes was equal to or less than 0.7 LogMAR. The latency of P100 was recorded monocularly using two check sizes of 15 and 60 min of arcs at two different levels of contrasts (30% and 100%). Results: P100 latency in amblyopic eyes was significantly increased compared to the normal group (P < 0.001). There was a significant difference (P < 0.001) in P100 latency in anisometropic and esotropic amblyopic eyes as compared to normal subjects, using high spatial frequency and with both levels of contrast. A significant difference was observed with large check sizes and high contrast between anisometropic amblyopic and normal eyes (P = 0.03). However, there was no significant difference between these two groups and the control group with other stimuli. Conclusion: The neural response based on p100 latency in PVEP was different between amblyopic groups and normal subjects. PVEP may be valuable for diagnosis, prognosis and treatment of amblyopia.